An Analysis Of Impoliteness Strategies Of Genshin Impact Player In 1st Anniversary Posted On Twitter - Fatimah Putri Sambada; Siti Zuhriah Ariatmi (Universitas Cokroaminoto Palopo, 2024)
This study aimed to analyse the strategy of impoliteness of Genshin Impact player on twitter using pragmatic approach. The purpose of this study was to find the type of impoliteness and function of impoliteness. The data for this research were taken from comments contained in the twitter @genshinimpact account. This study analysed based on the type of impoliteness strategies (Culpeper, 1996) and function of impoliteness proposed by Culpeper (2011). Related to the types of impoliteness, the result of the analysis show hat there are five types of impoliteness strategies in the comment ;(1) Bald on record impoliteness, (2) Positive impoliteness. (3) Negative impoliteness, (4) Sarcasms or mock politeness, (5) withhold politeness. Also, three functiones of impoliteness; (1) Affective impoliteness, (2) Coercive impoliteness, (3) Entertaining impoliteness. The utterances that show impoliteness are uttered by the player commented on twitter.